Psychometric Study of the Scale for the Assessment of Developmental Assets in the Neighborhood in a Sample of Chilean Adolescents - Vera-Bachmann, Daniela; Gálvez-Nieto, José L.; Trizano-Hermosilla, Italo; Salvo-Garrido, Sonia; Polanco, Karina (Frontiers in Psychology, 2020)
The Scale for the Assessment of Developmental Assets in the Neighborhood has demonstrated acceptable psychometric properties for its use in Spain and Chile; however, the original structure of five correlated factors and one second order factor is not yet completely clear. This study seeks to assess the psychometric properties of reliability and validity of the Scale for the Assessment of Developmental Assets in the Neighborhood in a sample of Chilean adolescents. A cross-sectional design was used with a sample 2,638 students (girls = 49.1%), with an average age of 15.79 years (SD = 1.35). The results obtained by exploratory and confirmatory factor analyses show that the best factor structure is the one with five correlated factors. The analysis of factorial invariance reflected that the degree of factorial equivalence between boys and girls is presented at the level of scale invariance. In addition, previous findings confirm that the Scale for the Assessment of Developmental Assets in the Neighborhood can be used in the Chilean context with slight modifications to the original version.